In vitro wound healing activity of sapium indicum willd leaf extracts - Abdul Aziz, Huwaida; Bakhtiar, M. Taher; Darnis, Deny Susanti; Zakaria, Zainul Amiruddin (African Ethnomedicines Network, 2015)
Background: Sapium indicum Willd (Euphorbiaceae) is traditionally used to accelerate wound healing process in Malay community. Objective: To evaluate wound healing potential of aqueous (AESI) and ethanolic extract of S. indicum leaves (EESI) using cell migration model. Methods: AESI and EESI were prepared using maceration techniques. The extracts were subjected to phytochemical screening, cytotoxicity (MTT assay) and scratch assay. Results: AESI contained saponins and tannins while EESI contained triterpenes, tannins and proteins. Based on MTT assay, AESI and EESI exhibited IC50 = 16.3 and 70.9 μg/mL, respectively. In the scratch assay, EESI caused significant (P< 0.05) concentration-dependent migration on 3T3 L1 cells whereas AESI exerted concentration-independent effect. Conclusion: The leaves of S. indicum exhibited wound healing potential and contained phytochemicals that may contribute to the activity. These findings would support potential use of S. indicum as wound healing plant.